Governance Disequilibrium: A Catalyst for Instability in Developing Countries: The Situation in Nigeria - Ogunwa, Samuel Adetola (Universitas Medan Area, 2025)
Democratic government is touted to reflect in democratic Governance, with the gains of Democracy being reflected in the day-to-day living standards of the citizenry. The lack of this is a consequence of governance disequilibrium, which in many instances has triggered political upheavals and socio-economic uncertainties in several countries. The paper argues that the Nigerian state has faced a governance crisis under both military regimes and democratic administrations. These governments are not well-reasoned, nor do they understand the enormous challenges of Governance ahead of them before assuming the responsibilities of government. While in office, they still struggled with doubt about their mission and how to address the situation. On the other hand, the subjects lack the socio-economic capacities to demand from those saddled with the responsibilities of the state what they have contributed to improving Governance, especially in areas such as emancipation and empowerment, alleviation of poverty, improvement of the standard of living, and security of life and property. The study concludes that governance disequilibrium is fundamental and a matter of time, which can be resolved when government officials see their appointments as a contrast and use their offices to legislate on national issues that will bring about change to socio-economic and political decadences across the Nigerian federation.